The Role of Quality Human Resources in the Development of Creative Industry to Improve Sustainable Economic Growth in Pematang Sera Village - Erwansyah, Erwansyah; Robain, Wilchan; Siregar, Mira Yosefa (Universitas Negeri Medan, 2023)
The purpose of this study was to identify and analyze the development of creative industries and the management of quality human resources in Pematang Serai Village, Tanjung Pura District, Langkat Regency in order to achieve sustainable economic growth. The specific objective of this study is to examine how the community, as human resources, can have a great deal of creativity and innovation in developing village potential, thereby contributing to the community's economy. Multiple linear regression analysis is used to evaluate the data. This study will employ a quantitative method related to data that characterizes the people of Pematang Serai Village, particularly household industry players involved in income growth. The study's findings indicate that the Creative Industry and Human Resource Management variables have a positive and statistically significant influence on the achievement of sustainable economic development. The influence contribution is 62.1% of the total